Genomics reveals broad hybridization in deeply divergent Palearctic grass and water snakes (Natrix spp.) - Schöneberg, Yannis; Winter, Sven; Arribas, Oscar; Di Nicola, Matteo Riccardo; Master, Maya; Owens, John Benjamin; Rovatsos, Michail; Wüster, Wolfgang; Janke, Axel; Fritz, Uwe (Molecular phylogenetics and evolution, 2023)
Understanding speciation is one of the cornerstones of biological diversity research. Currently, speciation is often understood as a continuous process of divergence that continues until genetic or other incompatibilities minimize or prevent interbreeding. The Palearctic snake genus Natrix is an ideal group to study speciation, as it comprises taxa representing distinct stages of the speciation process, ranging from widely interbreeding parapatric taxa through parapatric species with very limited gene flow in narrow hybrid zones to widely sympatric species. To understand the evolution of reproductive isolation through time, we have sequenced the genomes of all five species within this genus and two additional subspecies. We used both long-read and short-read methods to sequence and de-novo-assemble two high-quality genomes (Natrix h. helvetica, Natrix n. natrix) to their 1.7 Gb length with a contig N50 of 4.6 Mbp and 1.5 Mbp, respectively, and used these as references to assemble the remaining short-read-based genomes. Our phylogenomic analyses yielded a well-supported dated phylogeny and evidence for a surprisingly complex history of interspecific gene flow, including between widely sympatric species. Furthermore, evidence for gene flow was also found for currently allopatric species pairs. Genetic exchange among these well-defined, distinct, and several million-year-old reptile species emphasizes that speciation and maintenance of species distinctness can occur despite continued genetic exchange.
Keywords: hybridizace genetická; Hybridization, Genetic; vznik druhů (genetika); Animals; Phylogeny; Genomics; Reptilia; Colubridae; zvířata; Squamata; Speciation; fylogeneze; Natricidae; Genetic Speciation; Hybridization; genomika; Molecular clock